Technical Considerations of Pharmacokinetic Assays for LNP-mRNA Drug Products by RT-qPCR - Jason Pennucci; Amanda Hays; Wendy Adamowicz; Mitra Azadeh; Mohamed Benhammadi; Enric Bertran Portabella; MingLai Cheng; Kelly Colletti; Sanjay L. Dholakiya; Rajitha Doddareddy; Lara Duchstein; Jennifer Durham; et al. (The AAPS Journal, 2025)
Lipid nanoparticle-messenger RNA (LNP-mRNA) drug products are a growing class of drug modalities. The unique composition of these drug products requires multiple measurements to account for the different components of these drug modalities. Pharmacokinetic (PK) measurements include measurement of the encapsulated mRNA and components of the LNP in circulation to understand the effectiveness of the therapeutic mRNA. The PK measurements can utilize many different platforms including PCR. Current regulatory guidance documents for bioanalytical method validation are specific to ligand binding and chromatographic assay methods and difficult to interpret for use with molecular workflows. The purpose of this paper is to provide information on considerations for validation of regulated reverse transcription quantitative PCR (RT-qPCR) assays that are used to support the pharmacokinetic analysis of LNP-mRNA drug products. Graphical Abstract

Recommendations for Method Development and Validation of qPCR and dPCR Assays in Support of Cell and Gene Therapy Drug Development - Amanda Hays; Mark Wissel; Kelly Colletti; Russell Soon; Mitra Azadeh; Justin Smith; Rajitha Doddareddy; Melanie Chalfant; Wendy Adamowicz; Swarna Suba Ramaswamy; Sanjay L. Dholakiya; Sebastian Guelman; et al. (The AAPS Journal, 2024)
The emerging use of qPCR and dPCR in regulated bioanalysis and absence of regulatory guidance on assay validations for these platforms has resulted in discussions on lack of harmonization on assay design and appropriate acceptance criteria for these assays. Both qPCR and dPCR are extensively used to answer bioanalytical questions for novel modalities such as cell and gene therapies. Following cross-industry conversations on the lack of information and guidelines for these assays, an American Association of Pharmaceutical Scientists working group was formed to address these gaps by bringing together 37 industry experts from 24 organizations to discuss best practices to gain a better understanding in the industry and facilitate filings to health authorities. Herein, this team provides considerations on assay design, development, and validation testing for PCR assays that are used in cell and gene therapies including (1) biodistribution; (2) transgene expression; (3) viral shedding; (4) and persistence or cellular kinetics of cell therapies. Graphical Abstract

Deciphering the In Vivo Performance of a Monoclonal Antibody to Neutralize Its Soluble Target at the Site of Action in a Mouse Collagen-Induced Arthritis Model - Weirong Wang; Thomas S. McIntosh; Xiling Jiang; Rajitha Doddareddy; Elayne C. Dell; Honghui Zhou (Pharmaceutical Research, 2016)

Mechanistic Pharmacokinetic/Target Engagement/Pharmacodynamic (PK/TE/PD) Modeling in Deciphering Interplay Between a Monoclonal Antibody and Its Soluble Target in Cynomolgus Monkeys - Weirong Wang; Xiaofeng Wang; Rajitha Doddareddy; Damien Fink; Thomas McIntosh; Hugh M. Davis; Honghui Zhou (The AAPS Journal, 2014)